2020
DOI: 10.7717/peerj.10424
|View full text |Cite
|
Sign up to set email alerts
|

Ixodes scapularismicrobiome correlates with life stage, not the presence of human pathogens, in ticks submitted for diagnostic testing

Abstract: Ticks are globally distributed arthropods and a public health concern due to the many human pathogens they carry and transmit, including the causative agent of Lyme disease, Borrelia burgdorferi. As tick species’ ranges increase, so do the number of reported tick related illnesses. The microbiome is a critical part of understanding arthropod biology, and the microbiome of pathogen vectors may provide critical insight into disease transmission and management. Yet we lack a comprehensive understanding of the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 59 publications
3
19
1
Order By: Relevance
“…In comparison, tick samples showed a less diverse bacterial composition. This is likely to be due to the dominance of endosymbiont bacteria in the tick microbiome, which has been demonstrated in previous studies of the same tick species as identified in the present study [17, 18], and in tick species globally [66, 67]. The overall lack of similarity in bacterial communities between sample types observed in the present work has been reported in previous studies on small mammals and their vectors (ticks and fleas), indicating the complexity of microbial assemblages inhabiting these biological niches [65, 68, 69].…”
Section: Discussionsupporting
confidence: 74%
“…In comparison, tick samples showed a less diverse bacterial composition. This is likely to be due to the dominance of endosymbiont bacteria in the tick microbiome, which has been demonstrated in previous studies of the same tick species as identified in the present study [17, 18], and in tick species globally [66, 67]. The overall lack of similarity in bacterial communities between sample types observed in the present work has been reported in previous studies on small mammals and their vectors (ticks and fleas), indicating the complexity of microbial assemblages inhabiting these biological niches [65, 68, 69].…”
Section: Discussionsupporting
confidence: 74%
“…B. burgdorferi , B. miyamotoi , A. phagocytophilum and B. microti ) was compared with that of uninfected ticks. In the study by Gil et al. (2020) no significant differences were found in the alpha- and beta-diversity indices of the tick microbiome under single or co-infections with any of the pathogens tested ( Gil et al., 2020 ).…”
Section: Co-infections and The Tick Microbiomementioning
confidence: 84%
“…The nature of the relationship between pathogen co-infection and vector microbiome composition remains unclear. The association between microbiome composition and co-infections in ticks submitted for diagnostic testing was recently assessed ( Gil et al., 2020 ). The microbiome of whole I. scapularis nymphs and adults that tested positive for one, two or three tick-borne pathogens (i.e.…”
Section: Co-infections and The Tick Microbiomementioning
confidence: 99%
“…Out of these, 60,149 reads were assigned to ticks or eukaryotic organisms and were further discarded. As nymphal ticks are low biomass arthropods [ 75 , 76 ], the number of generated reads may be low on average, and variations in the read numbers can thus exist among samples. Moreover, such low biomass samples can be critically impacted by contamination originating from the various kits used to produce amplicons [ 77 ].…”
Section: Resultsmentioning
confidence: 99%